Kebutuhan Approach Light System pada Kedua Ambang Landasan Bandara Sultan Hasanuddin-Makassar untuk Meningkatkan Kapasitas Pergerakan Pesawat Udara - Endang Dwi Agustini (Research and Development Agency of The Ministry of Transportation, 2012)
In developing Sultan Hasanuddin Airport Makassar, one of the efforts is by installing Approach Light System, a navigation tool installed at both runway edges used to improve flight security and safety. By installing Approach Light System at both runway edges, it can guarantee safety flight in order to develop air traffic system in the movement area that is safe, fast and smooth.The objective of Approach Light System is to provide clear guides to pilots when performing landing on the runways. The tool is also useful for making accurate landing of the aircraft.By using descriptive qualitative technical approach method in the analysis of this study, it can be concluded that by completely installing the Approach Light System at both runway edges in Sultan Hasanuddin Airport, it has met the regulation number SKEP/114/VI/2002 on the Airport Installation System Standard Blueprint (Airfield Lighting System) issued by the General Directorate of Air Transport so that safe and secure flight can be conducted optimally and aircraft movement can be increased as well.Approach Light System merupakan peralatan navigasi pada kedua ambang landasan untuk meningkatkan keamanan dan keselamatan penerbangan. Tujuan dan manfaat dari Approach Light system adalah untuk memberikan tuntutan kepada pilot/penerbang saat melakukan pendaratan menuju landasan dan manfaatnya untuk ketepatan pendaratan pesawat udara.Melalui metode pendekatan teknis deskriptif kualitatif dalam melakukan analisis pembahasan dapat disimpulkan bahwa dengan terpenuhinya kebutuhan Approach Light system pada kedua ambang landasan bandara Sultan Hasanudin Makassar, maka sudah sesuai dengan ketentuan yang berlaku yaitu SKEP/114/VI/2002 yang diterbitkan oleh Direktorat Jenderal Perhubungan Udara tentang Standar Gambar Instalasi Sistem Bandar Udara (Airfield Lighting System) sehingga dapat terselenggara keamanan dan keselamatan penerbangan secara optimal dan dapat meningkatkan pergerakan pesawat udara.